Optimizing intraoperative imaging during proximal femoral fracture fixation – a performance improvement program for surgeons. Issue 2 (February 2018) - Rikli, Daniel; Goldhahn, Sabine; Blauth, Michael; Mehta, Samir; Cunningham, Michael; Joeris, Alexander; ,
Abstract: Introduction: Formal training for surgeons regarding intraoperative imaging is lacking. This project investigated the effect of an educational intervention focusing on obtaining and assessing a standardized lateral view of the proximal femur during intramedullary nailing of a pertrochanteric fracture. Materials and methods: Anatomical landmarks of the proximal femur that can be identified using intraoperative fluoroscopy and criteria for image quality, i.e. quality of projection were defined in a consensus process, followed by the development of educational materials and a 7-item checklist. Five surgeons from 5 Trauma Centers in 4 countries participated. Each surgeon a) assessed 5 of their own retrospective cases and 5 retrospective cases from 4 colleagues from their clinic, b) viewed an educational video and poster and re-assessed the same cases, and c) assessed the intraoperative images of 5 prospectively collected consecutive cases of their own and of colleagues afterwards. Results: The percentage of positive ratings for image quality increased from 72% prior to educational intervention to 88% after intervention (p < 0.001), and number of "not assessable" images decreased significantly. Percentage agreement between surgeons on the assessments increased from 75% to 87%. The proportion of best possible ratings for fracture reduction and implant position increased from 58% to 72% and from 49% to 66%, respectively. Percentage agreement between surgeons on assessment of reduction and implant position increased. Discussion and conclusions: A focused educational intervention can improve surgeons' ability to obtain and assess lateral view intraoperative images of the proximal femur and can improve the quality of reduction and implant positioning.